ANALISIS KESESUAIAN RPP DENGAN PRAKTIK PEMBELAJARAN DAN TINDAK LANJUT COACHING - Widiawati; Suardi; Idawati (STKIP Subang, 2025)
The urgency of this research stems from a specific problem, namely the gap between the lesson plan documents prepared by teachers and their implementation in classroom learning practices, particularly in aspects of time management, utilization of learning media, equitable student involvement, and implementation of the syntax of learning models. Various previous studies have explained the importance of quality lesson planning, but have not paid in-depth attention to how the mismatch between the lesson plan and actual practice affects the effectiveness of the learning process. This study aims to systematically analyze the alignment between the lesson plan and teacher learning practices, while simultaneously identifying the factors causing the mismatch and formulating recommendations for follow-up based on academic coaching. The research method used is a descriptive qualitative approach, utilizing analysis of lesson plan documents, classroom observations, and post-observation reflective interviews, then data analysis. The results show that although the lesson plan has been well-formulated administratively, there are implementation gaps, especially in the use of digital media due to technical constraints, less than optimal student participation, and the failure to fulfill all PBL syntax due to ineffective time management. These findings reveal an important pattern that good lesson planning does not guarantee quality implementation in the field. The implication of this research is that it emphasizes the importance of coaching-based academic supervision to improve alignment between learning planning and practice, and to encourage teachers to engage in continuous reflection.